Impact of microfinance on the livelihoods of rural communities: a case of VIRL Microfinance in Manicaland Province - Nyachoto, Samantha T.G. (Midlands State University, 2018)
The absence of traditional service providers (commercial banks) came the rise of microfinance institutions in marginalised rural areas. The main objective of the study is to evaluate the impact of microfinance on the livelihoods of rural people as a way of ensuring sustainable livelihood. The Makoni District in Manicaland Province was selected to be a case study of the impact of microfinance and VIRL a microfinance institution which is greatly active in the area. The microfinance institution’s mandate however, is to provide small loans that will improve household livelihoods of rural dwellers by financing income generating projects thus escaping the clutches of poverty. A quantitative research method was used to collect data from the provided micro-credit participants in the study area which enabled the researcher to acquire a rich pooled data for evaluation. As a result, the research indicated that microfinance does play a pivotal role which has a positive impact on rural livelihoods and household level. Thereby improving health care, education, savings culture and most importantly financially including the marginalised. Recommendations were also provided which include relaxation on collateral and application requirements like guarantors that will further sustain the livelihoods of the rural community in order to financially secure the already marginalised population.